Customer Preference Analysis: Why are R1 450VA Electricity Customers not Interested in Increasing Power? (A Case Study of PT PLN Batam Customers) - Siallagan, Asihon; Maharani, Anita; Maria, Maya (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the preferences of R1 450VA electricity customers at PT PLN Batam who are not interested in increasing their electricity capacity, even though a free program is available. The study aims to identify the factors influencing customers' decisions, including preferences, economic factors, the effectiveness of promotions, perceptions of benefits and risks, and long-term uncertainties. This research adopts SEM with PLS approach using SmartPLS 4 Software. Data were collected through questionnaires and interviews with active customers and internal documents from PT PLN Batam. Findings confirmed that service quality has a positive and significant effect on customer satisfaction and subsequently the decision to enhance their capacity. Additionally, the decision is also directly influenced by the economic capability. Furthermore, trust and promotion do not affect customer satisfaction directly in relation to the capacity increase program. Customer satisfaction is shown to mediate the relationship between several factors and the decision to enhance capacity. In summary, to improve customer participation, PT PLN Batam should prioritize enhancing the service quality, education and promotion strategies, customer profiling, uncertainty resolution, and trust building.